Propofol dose-finding to reach optimal effect for (semi-) elective intubation in neonates (2016)
Objective To define the effective dose for 50% of patients (ED50) of propofol for successful intubation and to determine the rate of successful extubation in those patients with planned intubation, surfactant administration, and immediate extubation (INSURE procedure). In addition, pharmacodynamic effects were assessed. Study design Neonates (n?=?50) treated with propofol for (semi-)elective endotracheal intubation were stratified in 8 strata by postmenstrual and postnatal age. The first patient in each stratum received an intravenous bolus of 1?mg/kg propofol. Dosing for the next patient was determined using the up-and-down method. A propofol ED50 dose was calculated in each stratum with an effective sample size of at least 6, via the Dixon-Masey method, with simultaneous assessment of clinical scores and continuous vital sign monitoring. Results Propofol ED50 values for preterm neonates <10 days of age varied between 0.713 and 1.350?mg/kg. Clinical recovery was not attained at the end of the 21-minute scoring period. Mean arterial blood pressure showed a median decrease between 28.5% and 39.1% from baseline with a brief decrease in peripheral and regional cerebral oxygen saturation. Variability in mean arterial blood pressure area under the curve could not be explained by weight or age. Conclusions Low propofol doses were sufficient to sedate neonates for intubation. Clinical recovery was accompanied by permissive hypotension (no clinical shock and no treatment). The propofol ED50 doses can be administered at induction, with subsequent up-titration if needed, while monitoring blood pressure. They can be used for further dosing optimalization and validation studies.